2006
DOI: 10.4049/jimmunol.176.4.2357
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans-Type Dendritic Cells Genetically Modified to Express Full-Length Antigen Optimally Stimulate CTLs in a CD4-Dependent Manner

Abstract: Oncoretroviral vectors encoding either full-length Ag or a corresponding immunodominant peptide were expressed in Langerhans-type dendritic cells (LCs) differentiated from CD34+ progenitors. We used human CMV as a model Ag restricted by HLA-A*0201 to define parameters for eventual expression of cancer Ags by LCs for active immunization against tumors. Stimulation by CMVpp65495–503-pulsed LCs, CMVpp65495–503-transduced LCs, and full-length CMVpp65-transduced LCs respectively increased tetramer-reactive T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This effect was not related to, or confounded by, antigen-specific activation of the CD4 ϩ T cells, as was demonstrated with purified CD8 ϩ T cells and with HLA A*0201-restricted 9-mer peptides matched with HLA A*0201 haplotype study subjects. A similar helper activity of CD4 ϩ T cells has previously been shown for CD8 ϩ T-cell priming to antigen-loaded adult LC (61). Although initial antigen stimulation via DC is considered sufficient to trigger CD8 ϩ T-cell differentiation, CD4 ϩ T cells are required to induce differentiation of the naïve CD8 ϩ T cells into functional memory cells (3).…”
Section: Fig 4 Priming Of Cd8mentioning
confidence: 90%
See 3 more Smart Citations
“…This effect was not related to, or confounded by, antigen-specific activation of the CD4 ϩ T cells, as was demonstrated with purified CD8 ϩ T cells and with HLA A*0201-restricted 9-mer peptides matched with HLA A*0201 haplotype study subjects. A similar helper activity of CD4 ϩ T cells has previously been shown for CD8 ϩ T-cell priming to antigen-loaded adult LC (61). Although initial antigen stimulation via DC is considered sufficient to trigger CD8 ϩ T-cell differentiation, CD4 ϩ T cells are required to induce differentiation of the naïve CD8 ϩ T cells into functional memory cells (3).…”
Section: Fig 4 Priming Of Cd8mentioning
confidence: 90%
“…HLA A*0201 tetramers refolded around HIV-1 p17 77-85 (SL9), EBV BMLF1280-288 (GL9), FLU M1 [58][59][60][61][62][63][64][65][66] (GL9), and CMV pp65 495-503 (NV9) were used to stain T cells that were stimulated by the peptide-loaded DC. In some experiments, the T cells were also surface stained with CD3-APC Cy7, CD8-Pacific blue, CD45 RA PE cyanin 7, CCR7-fluorescein isothiocyanate, CD27-PE (BD PharMingen), and tetramer-APC (Beckman Coulter, Fullerton, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, the polarization of Th1 cells is thought to contribute to cellular immune response and result in the increase of CD8+ cytotoxic T lymphocytes (CTLs); Th2 cell is associated with hormonal immune response and the increase of CD4+ helper T cells (Th) and memory T cells. Th and memory T cells play very important roles in maintaining the activity of CTLs during anti-tumor immune surveillance [14]. It has been reported that injection of Th2 cells into mice effectively repressed the tumor metastasis, increased T cells sensitivity to tumor antigens, and induced effective anti-tumor immune response [15,16].…”
Section: Introductionmentioning
confidence: 99%